(untitled) (Agro Productividad, 2024)
Objective: To estimate growth and yield variations in common beans (Phaseolus vulgaris L.) treated with a magnetized nutrient solution considering two factors: magnet exposure time and pH level. The significance of this crop lies in its nutritional and economic value. Design/Methodology/Approach: We used a hydroponic system with magnetized Steiner nutrient solution. The design was completely randomized, with a 4 x 6 factorial treatment arrangement and three replications. Factor A comprised exposure times (0.333 hours, 2 hours, chronic, and without magnetization), while Factor B covered solutions with different pH levels (3, 4, 5, 6, 7, and 8). We then applied a multiple regression analysis using the SAS software. Results: Models for vegetative growth variables (plant height, root length, root dry weight, and foliar biomass) and seed yield components (number of pods, number of grains per pod) were statistically significant (p<0.0001). Coefficients of determination ranged from 59.7 % to 82 %, percentages considered appropriate to explain the observed variability. Study limitations/Implications: While the models showed acceptable coefficients of determination, it is essential to consider other factors that were not assessed in this study: exposure to sunlight, insect influence, and diseases that could impact the responses of the bean crop. Findings/Conclusions: Appropriate models to describe vegetative growth and seed yield of the common bean, concerning magnetization time and nutrient solution acidity, include variables such as plant height, root length, root dry weight, foliar biomass, total biomass, number of pods, and number of grains per pod.